2019
DOI: 10.3390/s19204377
|View full text |Cite
|
Sign up to set email alerts
|

Single-Lead ECG Recordings Including Einthoven and Wilson Leads by a Smartwatch: A New Era of Patient Directed Early ECG Differential Diagnosis of Cardiac Diseases?

Abstract: Background: Smartwatches that are able to record a bipolar ECG and Einthoven leads were recently described. Nevertheless, for detection of ischemia or other cardiac diseases more leads are required, especially Wilson’s chest leads. Objectives: Feasibility study of six single-lead smartwatch (Apple Watch Series 4) ECG recordings including Einthoven (I, II, III) and Wilson-like pseudo-unipolar chest leads (Wr, Wm, Wl). Methods: In 50 healthy subjects (16 males; age: 36 ± 11 years, mean ± SD) without known cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 11 publications
0
66
0
1
Order By: Relevance
“…As an interesting finding, the mean age of our included patients was 63.6 ± 14.0 years, which reflects an older age in comparison to other studies [ 14 , 15 ]. This is important because one might think that it would be very difficult for the elderly to record ECG with a smartwatch, but our experience showed that the elderly without motor or mental problems could undertake this task confidently after a very short training.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…As an interesting finding, the mean age of our included patients was 63.6 ± 14.0 years, which reflects an older age in comparison to other studies [ 14 , 15 ]. This is important because one might think that it would be very difficult for the elderly to record ECG with a smartwatch, but our experience showed that the elderly without motor or mental problems could undertake this task confidently after a very short training.…”
Section: Discussionmentioning
confidence: 48%
“…Although we are not the first group who reported the utility and description of this technique, our study has confirmed its validity in a relatively large sample. Our previous understanding regarding the smartwatch ECGs were limited to the findings of several case reports and case series [ 7 , 27 , 28 , 29 , 30 ], and three studies on around 50–100 patients [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations